Disseminating Knowledge to Providers on Exercise Training After Solid Organ Transplantation. (June 2020) - Janaudis-Ferreira, Tania; Mathur, Sunita; Tansey, Catherine M.; Blydt-Hansen, Tom; Hartell, David
Introduction: The objectives of our dissemination project were (1) to disseminate the evidence supporting exercise training in solid organ transplantation to exercise professionals, health-care professionals, physicians, and directors of transplant programs in order to enhance their ability to apply evidence to practice and (2) to build a community of exercise professionals and researchers across Canada. Methods: We used the 5-step Patient-Centered Outcomes Research Institute model for knowledge translation to guide our project: (1) evidence assessment, (2) audience and partner identification, (3) dissemination, (4) implementation, and (5) evaluation. After meeting with experts in the field, conducting a literature review, and identifying an appropriate audience, we took our presentations on the road across Canada. Results: We visited 10 transplant centers and held interactive knowledge translation sessions in each center. To provide sustainability and to facilitate the adoption of the research evidence, we founded the Canadian Network for Rehabilitation and Exercise for Solid Organ Transplant Optimal Recovery network and created its website. Conclusions: Our project raised awareness of the importance of exercise among many health professionals in Canada and built a community of exercise professionals and researchers in the field of transplantation through the rehabilitation network. It also led to the creation of online resources that will facilitate the implementation of rehabilitation programs in transplant centers.